Role of welding residual stress in stainless steel piping with application of the leak-before-break technology - Liu, Zhenshun; Zhang, Sheng; Mao, Qing; Zheng, Xiang Yuan (Frontiers in Energy Research, 2023)
The predicted leakage rate of piping circumferential through-wall cracks (CTWC) under various loading levels is a critical factor for the application of leak-before-break (LBB) technology. In current engineering approaches, the effect of welding residual stress has not been carefully taken into account. In this paper, both numerical analyses and comparative verification are adopted to examine the influence of typical welding residual stress field on the crack opening displacement for austenitic stainless steel piping with representative geometric dimensions and in situ measured material performance curves. An in-depth investigation is carried out to reveal the effect of the residual stress on morphological parameters of the CTWC flow channel. In the case where the residual internal stress of welding has the greatest effect, the Henry-Fauske model is employed to analyze the flow medium passing through the CTWC and the corresponding leak rate for a typical nuclear power plant. The results indicate that the welding residual stress leads to a substantial change in the crack opening displacement and crack morphology parameters. Both the current GE/EPRI method and the NUREG/CR-6837 modification recommended by the American Electric Power Research Institute underestimate the effect of this phenomenon, resulting in a higher prediction of the medium leakage rate. A similar situation is most likely to occur for the cases of short cracks in thin-walled piping and long cracks in thick-walled piping. Additionally, the obtained results reveal that the welding residual stress causes the whole crack surface to open negatively, and the axial line of the long crack on the thick-walled piping is close to a conic curve under specific conditions.